The emergence of a research agenda on the standardization of accounting sustainability and climate-related reporting in the public sector - Azevedo, Ricardo Rocha de; Sediyama, Gislaine Aparecida Santana; Aquino, André Carlos Busanelli de (Advances in Scientific and Applied Accounting, 2024)
This editorial delves into Brazil's status regarding the adoption of accounting standards for sustainability and explores the emerging research agenda on this subject. Public sector sustainability reporting has recently sparked international debate and has carved out its niche as an emergent research agenda within broader topics such as "accounting reform" or "adoption of accounting standards" in the public sector. While aligning with accounting standards in the public sector echoes past phenomena like Brazil's experience with implementing IPSAS international accounting standards, this movement faces unique challenges, such as a lack of consensus and understanding on the topic, as well as the imperative to involve other epistemic communities throughout various phases of the change. This study also highlights research opportunities, particularly given that the adoption process is still nascent.